I'm not a chocolate farmer, I'm just a housewife" - Gendered divisions of labor for small-scale cacao production in Lampung and South-Sulawesi, Indonesia - Eissler, Sarah (Pennsylvania State University, 2019)
Presented by Sarah Eissler (Penn State University), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.